Contribution of the Mexican food agroindustry to the gross domestic product during 1993-2019 - Moctezuma-López, Georgel (Revista Mexicana de Ciencias Agrícolas, 2023)
This research aimed to quantify the contribution of the Mexican food agroindustry to the national gross domestic product, as well as to calculate the average annual growth rate during a 27-year period from 1993 to 2019, which considered the last four six-year periods, and to determine the contribution to the manufacturing industry and the national economy. The methodology was documentary with the following stages: i) selection of the topic to be studied; ii) collection of information from secondary documentary sources, which was mainly from the national accounts of INEGI; iii) preparation of the research plan; iv) information organization, using the North American Industry Classification System of the National Institute of Geography and Informatics; and v) use of the statistical function, which for this case was the average annual growth rate. It was found that the food industry presented a positive trend throughout the period, with an average annual growth rate of 2.21% and with a parallelism with the manufacturing industry, which is the sector that encompasses the food industry; however, the latter presented some falls in its growth. The most relevant agroindustry in relation to the contribution of food GDP was the preparation of bread and tortilla with 30.15%, essential products of the basic basket in the diet of the people of Mexico. Finally, the food industry, on average for the period, contributes 22.42% of the manufacturing gross domestic product and 3.72% of the national product.
Keywords: average annual growth rate; growth; six-year periods; trends